Anti-influenza virus activities of 4-substituted 2,4-dioxobutanoic acid inhibitors. - Hastings, J C (1996)
We previously identified a series of compounds which specifically inhibited the transcription of influenza A and B viruses (J. Tomassini, H. Selnick, M.E. Davies, M.E. Armstrong, J. Baldwin, M. Bourgeois, J. Hastings, D. Hazuda, J. Lewis, W. McClements, G. Ponticello, E. Radzilowski, G. Smith, A. Tebben, and A. Wolfe, Antimicrob. Agents Chemother. 38:2827-2837, 1994). The compounds, 4-substituted 2,4-dioxobutanoic acids, selectively targeted the cap-dependent endonuclease activity of the transcriptase complex. Additionally, several of these compounds effectively inhibited the replication of influenza virus but not other viruses in cell culture assays. Here, we report on the anti-influenza virus activities of other potent derivatives of the series evaluated in both in vitro and in vivo infectivity assays. These compounds inhibited the replication of influenza virus in yield reduction assays, with 50% inhibitory concentrations ranging from 0.18 to 0.71 microM. These 50% inhibitory concentrations were similar to those observed for inhibition of in vitro transcription (0.32 to 0.54 microM). One selected compound also elicited a dose-dependent inhibition of influenza virus replication in mice following an upper respiratory tract challenge. These studies demonstrate the antiviral efficacy of this inhibitor class and thereby establish the utility of influenza virus endonuclease as a chemotherapeutic target.